Intelligent Antenna Array Systems for Modern Communication Networks - yahiea alnaiemy; Mohammed N. Majeed; Mohsin Ali Ahmed; Taha A. Elwi; Sarah Mohemmed Fawzi Hussein (Academic Science Journal)
In last two decades, Smart Antenna Systems (SAS) as well as Multiple Input Multiple Output (MIMO) systems have emerged as strong and efficient contenders for 5G wireless communication networks due to the advantages they may bring based on the improvements in transmission and reception of electromagnetic signals with respect to omnidirectional antennas. Although there is a fair amount of academic software previously available in this field, cross-use systems simulators do not utilize sufficient wireless system requirements to implement all requirements, and therefore, they do not provide the opportunity to emulate on the broadest lines where SAS or MIMO is more widely used. In this work, a new idea will be formed to improve MIMO 5th generation (5G) smart antenna using adaptive equalizer technology. This new proposal will appear distinctly and noticeably to improve the performance and efficiency of transmission and reception, in addition to its high sensitivity.